Sakra in Early Buddhist Art - Anderson, Leona (My University, 1978)
The following thesis traces the development of Indra/Sakra in Buddhist iconography in India up to the third century A.D. The change in representations of Indra/Sakra parallels a larger evolution of popular Buddhism itself from a religious system, in which the figure of the historical Buddha was predominant, into a devotional cult centered on the figures of both the historical Buddha and numerous boddhisattvas. The study thus highlights one aspect of this shift in emphasis from early Hinayana Buddhism to Mahayana Buddhism. Art forms in conjunction with relevant texts provide the context in which Indra appears in early Buddhist art (around the first century B.C.E) and his subsequent development in Mahayana art (early Gandhara and Mathura).
The first chapter reviews the character of Indra in non-Buddhist contexts: the Vedic and Epic traditions. Evidence from these periods provides the context out of which the Buddhist Sakra emerged. The Vedic Indra developed into the Epic Indra from which the Buddhist Sakra seems to have evolved.
At the early Buddhist sites of Saffichi and Bharhut Sakra emerges as a devotee of the Buddha. He appears in iconography and relevant texts, in a narrative context as one of several characters in the Jataka tales. He is identifiable either by his iconographic form (a royal figure who sometimes wears a cylindrical crown specific to him and who carries a vajra and/or jar of amrta), or by virtue of the context in which he appears.
At Gandhara and Mathura Sakra becomes a figure of greater complexity who is often removed from any narrative context. Sakra and Brahma attend the Buddha in prototypical representations of the Buddhist triad (the Buddha and two boddhisattvas). This triad signals an important development in the art and theology of Buddhism. It is indicative of the development of the worship of the Buddha as the main object of devotion acompanies by Sakra and Brahma in early Buddhism and by boddhisattvas in the later tradition. It is the emergence of these latter figures in this role which represents the most significant change in popular Buddhism in India which was to be transmitted to the Far East. The Buddha has become a transhistorical figure worshipped independent of a narrative context. His attendants though they still adore the Buddha are lifted from a narrative context attaining the status of Buddhist deities.
In addition, Sakra is intimately related to the vajra-bearer who emerges at Gandhara. The context in which this latter figure appears, his function, and his primary attribute, the vajra, indicate the nature of this relationship. This iconographic form may be prototypical of the later boddhisattva Vajranani and certainly is the basis of the Nio who appear as fierce guardian figures in iconography in Japan and China.
These two developments reflect the emergence of Mahayana Buddhism and are indicative of the directions it will take as it grows and develops in India, where it arose, and outside of India, in China and Japan.
Keywords: Religion; Religion